2015
DOI: 10.1063/1.4930834
|View full text |Cite
|
Sign up to set email alerts
|

Monolithic fabrication of quasi phase-matched waveguides by femtosecond laser structuring the χ(2) nonlinearity

Abstract: We demonstrate second harmonic generation in quasi phase-matched waveguide structures fabricated by direct laser writing. Circular waveguides are inscribed in z-cut lithium niobate that provide well confined guiding of the fundamental and second harmonic wave. In contrast to classic schemes that employ periodically poled crystals, quasi phase-matching is realized by a laser-induced modulation of the nonlinearity inside the waveguide core. The proposed design allows monolithic integration of buried frequency co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…6 We have used this technique recently to fabricate integrated quasi-phase matched waveguides in LiNbO 3 . 7 The advantage of this method is that the nonlinearity can be modulated in three dimensions (3D). 8 However, due to the weak modulation of the nonlinearity, the conversion efficiency is smaller compared with electrically inverted ferroelectric domain structures.…”
mentioning
confidence: 99%
“…6 We have used this technique recently to fabricate integrated quasi-phase matched waveguides in LiNbO 3 . 7 The advantage of this method is that the nonlinearity can be modulated in three dimensions (3D). 8 However, due to the weak modulation of the nonlinearity, the conversion efficiency is smaller compared with electrically inverted ferroelectric domain structures.…”
mentioning
confidence: 99%
“…Recently, Kroesen et al demonstrated quasi-phase-matched (QPM) waveguides using the modulation of the χ (2) nonlinearity within the coherence length rather than typical domain inversion of periodically poled lithium niobate [83]. By writing a depressed cladding waveguide and an internal 6.7 mm pitch multiscan grating (Figure 24), the authors were able to demonstrate 5% second harmonic conversion from 1064 to 532 nm.…”
Section: Lithium Niobatementioning
confidence: 99%
“…In general, fs-laser written waveguides in LN can be categorized into three groups depending on the mechanism of optical guiding: positive-refractive-index(RI)-induced [9][10][11][12][13] , stress-induced [14][15][16][17][18] , and depressed-cladding waveguides 14,[19][20][21][22][23][24] . The focus of this study is on the fabrication and optimization of waveguides of the third type, which present a number of advantages over the first two types, including higher thermal stability, output-profile controllability and low input-polarization dependence.…”
Section: Introductionmentioning
confidence: 99%